1937
DOI: 10.1073/pnas.23.9.484
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Induced Breaks in Chromosomes of Drosophila Melanogaster

Abstract: Lethal larvae of the mutation Igl in Drosophila melanogaster form puparia, but this process is greatly retarded as compared with normal larvae. It is shown that puparium-formation can be accelerated by transplantation of a normal ring-gland to lethal larvae. There is therefore evidence that the ring-gland is an organ of internal secretion and produces a pupation hormone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1938
1938
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Males also carry a submetacentric or metacentric Y chromosome. Salivary gland nuclei show six long banded euchromatic arms, consistent with earlier reports; [30][31][32][33] no banding is detected on the 4 th chromosome, suggesting that it is heterochromatic. In the meiotic nuclei of primary spermatocytes, a tetravalent between X, Y and 4 th chromosomes is observed in all species of the ananassae subgroup except the three members of the ercepeae complex (D. merina, D. vallismaia and D. ercepeae) ( Fig.…”
Section: Resultssupporting
confidence: 91%
“…Males also carry a submetacentric or metacentric Y chromosome. Salivary gland nuclei show six long banded euchromatic arms, consistent with earlier reports; [30][31][32][33] no banding is detected on the 4 th chromosome, suggesting that it is heterochromatic. In the meiotic nuclei of primary spermatocytes, a tetravalent between X, Y and 4 th chromosomes is observed in all species of the ananassae subgroup except the three members of the ercepeae complex (D. merina, D. vallismaia and D. ercepeae) ( Fig.…”
Section: Resultssupporting
confidence: 91%
“…This could be due to some aspect of the structure of IH or to the fact that these regions simply contain more DNA than other regions, DNA that is more highly compacted in polytene chromosomes. Kaufmann and Demerec (1937) concluded that break frequency in the heterochromatic Y chromosome was proportional to the length of this chromosome in metaphase. Further analysis of a wealth of cytological material (Bauer et al 1938;Kaufmann 1946) demonstrated that break frequency in the pericentric heterochromatin and euchromatic arm of the X chromosome is also proportional to the respective lengths of the heterochromatic region and the euchromatic arm of this chromosome during mitosis.…”
Section: Does Ectopic Pairing Results From Underreplication?mentioning
confidence: 99%
“…(I) The behavior of heterochromatic parts is still open to discussion. KAUFMANN and DEMEREC (1937) from their data on break frequencies in Y sperms, have reached the conclusion that there is in all chromosomes including the Y a breakage frequency directly proportional to their metaphase length. From this they further conclude that the chromonema length is directly proportional to metaphase length, as suggested by MULLER and PAINTER (1932); moreover that the Y therefore is of the same general structure as euchromatic chromosomes, and that direct proportionality exists between chromonema length and breakage numbers in all chromosome parts.…”
Section: Discussionmentioning
confidence: 99%